Smoking Makes Treatment of Cancer Less Effective - Nagem, Elhaitham (Libyan International Medical University Faculty of AMS, 2022)
Cancer is diseases in which abnormal cells divide without control and can invade nearby tissues. Cancer cells can also spread to other parts of the body through the blood and lymph systems. There are several main types of cancer. Carcinoma is a cancer that begins in the skin or in tissues that line or cover internal organs. Sarcoma is a cancer that begins in bone, cartilage, fat, muscle, blood vessels, or other connective or supportive tissue. Several forms of cancer are caused by smoking. Lung, bladder, cervix, kidney, larynx (voice box), pharynx (upper throat), nose, mouth, esophagus (food pipe), pancreas, stomach, liver, and several forms of leukemia are all linked to smoking. Also included are smokers. Smokers are seven times more likely than nonsmokers to die from these cancers. Scientists have discovered Tobacco smoke contains almost 4,000 distinct compounds. Smoking throughout cancer treatment is associated with a variety of adverse events that include greater mortality, and more treatment related complications, there is little research on the effect of smoking on cancer treatment–related side effect severity and symptom burden. The primary aim of this study was to determine the effect of smoking on the total symptom burden, the sum of 12 common treatment-related side effects, in patients undergoing treatment for cancer.